Room temperature plasticity and phase transformation of nanometer-sized transition alumina nanoparticles under pressure. (15th May 2018) - Issa, I.; Joly-Pottuz, L.; Réthoré, J.; Esnouf, C.; Douillard, T.; Garnier, V.; Chevalier, J.; Le Floch, S.; Machon, D.; Masenelli-Varlot, K.
Abstract: A powder of transition alumina nanoparticles (including γ and a so-called δ-type) is compacted at room temperature in a diamond anvil cell (DAC) under pressures ranging from 5 GPa to 20 GPa. Characterization carried out on thin foils prepared by focused ion beam (FIB), from the compacted powder, unambiguously reveals plasticity. High resolution transmission electron microscopy (HRTEM) and electron diffraction also evidence phase transformation of nanoparticles under high pressure and nanoparticles show faceting parallel to the loading direction with a preferential crystallographic orientation of the facets corresponding to {220} planes of γ−Al2 O3 . It can also be deduced, from the comparison between the DAC experiments and in situ TEM nano-compression tests on single particles performed in a preceding work, that plasticity is driven by slip bands corresponding to {111} slip planes, common for a spinel structure, such as, for instance, γ−Al2 O3 . We also demonstrate that at ambient temperature the transition alumina phase is also prone to structural change under high pressures with the following sequence γ-Al2 O3  →  δ * Al2 O3, these two phases coexisting, sometimes, in the same nanoparticle after compaction. Plasticity at room temperature in alumina nanoparticles and the subsequent phase transformation under pressure may have strong impacts on the process of alumina nanostructured ceramics. Graphical abstract: Image 1